Comparative study of uric acid levels in diabetes mellitus and metabolic syndrome - B.SAI RAVI KIRAN,; T.MOHANALAKSHMI,; R.SRIKUMAR,; E.PRABHAKAR REDDY, (International Journal of Pharma and Bio Sciences, 2016)
Diabetes mellitus (DM) is a systemic metabolic disorder characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. The metabolic syndrome consists of a constellation of metabolic abnormalities.Serum Uric acid (UA) level has been suggested to be associated with factors that contribute to the metabolic syndrome. However the association between serum UA level and number of components that contribute to the metabolic syndrome and DM (diabetes mellitus) was associated most with higher serum UA level. This study compared the serum Uric Acid Levels in Diabetes Mellitus and Metabolic Syndrome. The Present study was carried out in the department of Biochemistry, Sri Lakhsmi Naryana Institute of Medical Sciences, Puducherry. The present study was conducted on 200 patients with Type II diabetes mellitus, 200 patients with metabolic syndrome, and 200 patients with controls as per IDF criteria and waist circumference. Serum uric acid levels are elevated when compare to other parameters (FBS, HbA1C, LDL-C, Urea, Creatinine, TGL, Lipoprotein (a)). This facilitates the claim that serum uric acid in association with the lipid ratios could serve as simple and economically viable biochemical marker. UA have a strong association with Diabetes and Metabolic syndrome.